2017
DOI: 10.1002/2016gl072266
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian identification of multiple seismic change points and varying seismic rates caused by induced seismicity

Abstract: The Central and Eastern United States (CEUS) has experienced an abnormal increase in seismic activity, which is believed to be related to anthropogenic activities. The U.S. Geological Survey has acknowledged this situation and developed the CEUS 2016 1 year seismic hazard model using the catalog of 2015 by assuming stationary seismicity in that period. However, due to the nonstationary nature of induced seismicity, it is essential to identify change points for accurate probabilistic seismic hazard analysis (PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
(39 reference statements)
3
10
0
Order By: Relevance
“…1 C ). Focusing on the mainshocks, we followed the declustering approach of Reasenberg (29) recently applied to seismicity catalog in Oklahoma (16, 30, 31) to remove the dependent earthquakes and identify the events directly linked to deep fluid injection ( SI Appendix , Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 C ). Focusing on the mainshocks, we followed the declustering approach of Reasenberg (29) recently applied to seismicity catalog in Oklahoma (16, 30, 31) to remove the dependent earthquakes and identify the events directly linked to deep fluid injection ( SI Appendix , Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the amplitude of the seismicity rate showed a larger sensitivity to D than to t crit . Noteworthy, the half-year uncertainty chosen for the t crit sensitivity test is reasonably well-constrained by observation (31). Table 1 summarizes the overall conclusions reached following the sensitivity tests on model parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The number of slip rate changes is limited by a reversible‐jump algorithm that favors simple solutions (Sambridge et al., 2006). Bayesian techniques are often applied to deal with uncertainty associated with limited data (Amey et al., 2019; Bronk Ramsey, 2009; Montoya‐Noguera & Wang, 2017). Several different Bayesian MCMC approaches have been developed for modeling cosmogenic data from fault scarps (Beck et al., 2018; Tesson & Benedetti, 2019; Tikhomirov et al., 2011).…”
Section: Methodsmentioning
confidence: 99%
“…In order to model slip rate and the pattern of exhumation through time, we use a modified version of the Bayesian MCMC approach developed by Cowie et al (2017) to explore the age-slip relationships that adequately explain the observed 36 Cl measurements within uncertainties (further described later in this section, the supporting information, and available online, github.com/lcgregory/SimpleSlips). Bayesian statistical methods are widely applied in earth science and geochronology in order to incorporate prior information and calculate the posterior distribution for a set of parameters given quantitative measurements, using a mathematical model (Bronk Ramsey, 2009;Montoya-Noguera & Wang, 2017). Bayesian inversions can also be transdimensional, meaning that the number of model parameters ("unknowns") for which we solve is allowed to vary, increasing or decreasing the complexity of the model depending on what is required by the data (Amey et al, 2019;Bodin & Sambridge, 2009;Dettmer et al, 2010;Green, 1995;Sambridge et al, 2006).…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…Along with these improvements the number of detected arrivals generally increases approximately by an order of magnitude per decreasing magnitude unit of sensitivity, introducing new challenges into the earthquake detection pipeline. Converting high rates of arrival picks into an accurate earthquake catalog can be invaluable in seismology, since dense catalogs improve our understanding of seismogenic processes occurring at plate boundaries (Kato and Nakagawa, 2014;Delorey et al, 2015), allow for monitoring rate changes of seismicity (Montoya-Noguera and Wang, 2017;Fiedler et al, 2018), improve resolution of tomographic images (Peng and Ben-Zion, 2005;Watkins et al, 2018), reveal dynamic triggering and anthropogenic induced seismicity (Shapiro et al, 2006;Hill and Prejean, 2007;Peng et al, 2009;Ellsworth, 2013), and may contain information regarding the timing of future earthquakes (Rouet-Leduc et al, 2017;Lubbers et al, 2018). Dense catalogs also provide new datasets that can be incorporated into increasingly popular machine learning approaches for a variety of applications in seismology (DeVries et al, 2018;Perol et al, 2018;Ross et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%